CULTURAL DIMENSIONS ON ESG FACTORS AND FINANCIAL PERFORMANCE INTERNATIONAL CONTEXT - Prayoga, Hadiyan; Badruzaman, Jajang; Rina Andriani, Rd Neneng; Hermansyah, Iwan (Akurasi : Jurnal Studi Akuntansi dan Keuangan, 2025)
Motivated by the global inconsistency in ESG performance outcomes, this research clarifies whether cultural differences explain such variations.  This study examines how national culture shapes the relationship between ESG dimensions and financial performance across countries. Using a quantitative approach with OLS regression on 13,608 firm-year observations from 43 countries, the findings reveal that environmental performance is largely unaffected by cultural traits, while social and governance dimensions exhibit culture-dependent effects. Specifically, social initiatives gain a stronger financial impact in high power distance and masculine societies, and governance consistently enhances firm performance. The study contributes by integrating cultural dimensions into firm-level ESG analysis, offering practical insights for investors and policymakers to design culturally aligned ESG strategies that enhance sustainability effectiveness.